2014
DOI: 10.1039/c4sm01920b
|View full text |Cite
|
Sign up to set email alerts
|

Turning up the heat on wormlike micelles with a hydrotopic salt in microfluidics

Abstract: In equilibrium, wormlike micelles can transition from entangled to branched structures with increasing surfactant concentrations and ionic strength. Under flow conditions, structural transition of micellar solutions can follow very different trajectories. In this study we consider the flow of a semi-dilute wormlike micellar solution through an array of microposts, with focus on its rheological and microstructural evolutions. Specifically, the micellar solution (precursor) contains cationic surfactant cetyltrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…It was shown that at polymer concentrations 3–4.5 wt % corresponding to regime II the samples always contain spherical microdomains immersed in a matrix of densely packed wormlike surfactant chains often arranged parallel to each other, forming bundles and bundle-like loops (Figure ). Similarly arranged micellar chains were previously visualized in many wormlike micellar solutions , and in supramolecular polymers . Here we observe numerous microdomains included in such matrix.…”
Section: Resultssupporting
confidence: 80%
“…It was shown that at polymer concentrations 3–4.5 wt % corresponding to regime II the samples always contain spherical microdomains immersed in a matrix of densely packed wormlike surfactant chains often arranged parallel to each other, forming bundles and bundle-like loops (Figure ). Similarly arranged micellar chains were previously visualized in many wormlike micellar solutions , and in supramolecular polymers . Here we observe numerous microdomains included in such matrix.…”
Section: Resultssupporting
confidence: 80%
“…For sodium chloride, the addition of 0.2 wt % salt induced a slope of q –3 at low q . Such a slope at low values of q is often interpreted as accompanying phase separation, but it can also be indicative of the formation of a gel-like network with fractal characteristics . Notably here, the addition of 0.2 wt % NaCl did not induce obvious phase separation, with the sample remaining clear and optically isotropic, but the addition of 1.0 wt % NaCl did result in phase separation, wherein a dense gel-like EAPB-rich phase separated as a supernatant above an inviscid excess water phase.…”
Section: Resultsmentioning
confidence: 61%
“…Since semidilute micellar solutions usually possess weak viscoelasticity, they are more desirable for oil recovery and encapsulation related applications with higher mobility. Moreover, cationic surfactant solutions with organic salts in the semidilute regime have shown not only interesting rheological behaviors [Ouchi et al (2007); Shikata et al (1987); Vasudevan et al (2008)] but also exhibited unique capabilities in forming irreversible nanostructured phases [Cardiel et al (2013);Cardiel et al (2014b); Dubash et al (2011);Vasudevan et al (2010)] for encapsulation and sensing applications [Cardiel et al (2014a); Lu et al (2010)]. Motivated by the temperature sensitive nature of SHNC and the advantage of semidilute wormlike micellar solutions, this work focuses on the rheological behavior of aqueous CTAB/SHNC mixtures in the semidilute regime, in which micelles are positively charged and isotropically distributed.…”
Section: Introductionmentioning
confidence: 99%